Effect of alcohol interventions on suicidal ideation and behaviour: A systematic review and meta-analysis. (1st September 2021) - Witt, Katrina; Chitty, Kate M.; Wardhani, Rachmania; Värnik, Airi; de Leo, Diego; Kõlves, Kairi
Highlights: Interventions limiting alcohol use led to reduction in self-harm/suicide attempt. Interventions limiting alcohol use do not have impact on suicidal ideation. There is no significant difference in effect by therapeutic approach. Abstract: Background: Alcohol consumption is related to both suicidal ideation and behaviour, but evidence regarding the effect of psychological interventions to reduce alcohol use on self-harm, suicidal behaviour and ideation is limited. Therefore, the aim of the current study was to conduct a systematic literature review and meta-analysis of the effect of alcohol-related psychological interventions on these outcomes at the individual level. Methods: We searched the Cochrane CENTRAL, Cochrane DARE, EMBASE, Medline, ProQuest, PsycINFO, PubMed, SCOPUS, and Web of Science electronic databases to 5 January 2021. We included all English-language papers worldwide utilising psychological interventions with a focus on harmful alcohol use and suicidal ideation, self-harm, and/or suicidal behaviour. Results: We identified 11 studies, nine provided sufficient numerical data for meta-analysis. Although the methods and effect sizes varied substantially in the studies, reducing alcohol may led to a reduction in self-harm and suicide attempt by the final follow-up assessment (Odds ratio [OR] 0.57, 95% confidence interval [CI] 0.33 to 0.97, 6 studies, 491 participants, I 2 = 0%). However, there was no apparent effect for these interventions on suicidal ideation or suicide deaths. There was no significant difference in effect by therapeutic approach. Neither intervention dose (in hours) nor duration (in months) significantly explained differences in treatment effectiveness. Conclusions: Interventions targeting harmful alcohol consumption may contribute towards a reduction in self-harm at the individual level. However, there was no apparent effect of these interventions on suicidal ideation (measured either continuously or dichotomously) or suicide deaths.